Fatal acquired coagulation factor V deficiency after hepatectomy for advanced hepatocellular carcinoma as a possible immune checkpoint inhibitor-related adverse event: a case report - Shintaro Arakaki; Shinichiro Ono; Futoshi Kawamata; Shinichiro Ishino; Yasunori Uesato; Tomo Nakajima; Yukiko Nishi; Satoko Morishima; Shingo Arakaki; Tatsuji Maeshiro; Masayoshi Souri; Akitada Ichinose; et al. (Surgical Case Reports)
Abstract Background Atezolizumab plus bevacizumab therapy was recently introduced as the first line for unresectable advanced hepatocellular carcinoma (HCC), but immune-related adverse events (IrAEs) due to atezolizumab are a great concern. Here, we report the case of a patient who developed fatal acquired coagulation factor deficiency after hepatectomy for HCC, treated with atezolizumab and bevacizumab before surgery. Case presentation A 70-year-old man received right trisegmentectomy of the liver with hepaticojejunostomy for advanced HCC with bile duct invasion, after atezolizumab and bevacizumab therapy. The patient suffered the sudden onset of severe multiple coagulation factor deficiency (II, V, VII, VIII, IX, X, XI and XII) immediately following reoperation for anastomotic leakage of hepaticojejunostomy, 7 days after hepatectomy. The coagulation factor deficiency did not reverse even with intensive treatment, and the patient died of uncontrollable bleeding 32 days after hepatectomy. An IrAE due to atezolizumab was suspected because the patient had developed the possible IrAE of enthesitis of the right gastrocnemius muscle before surgery, and specific inhibitors against factor V and anti-factor V autoantibodies were detected, leading to an ultimate diagnosis of autoimmune FV/5 deficiency (AiF5D). Conclusion Severe acquired coagulopathy should be recognized as a possible life-threatening IrAE when using atezolizumab and bevacizumab for HCC.